The Effects of Reading Assistant Software on the Speech Fluency and Accuracy of EFL University Students - Kitjaroonchai, Nakhon; Maywald, Suzanna (JET (Journal of English Teaching), 2024)
This study investigated the effects of a reading assistant software on the fluency and accuracy of speech production among EFL university students, employing a one-group pretest-posttest design. The participants included 50 Thai undergraduate English majors in their first and second years. Data were analyzed using paired-samples t-tests to measure L2 oral fluency, specifically pruned speech rate (PSR) and mean length of run (MLR). Accuracy rate was assessed by quantifying the proportion of error-free clauses within the participants’ speeches from the pretest and posttest and calculating the average number of error-free clauses per T-unit. Results indicated significant improvements in speech fluency, evidenced by longer uninterrupted speech segments, fewer disfluencies like filled pauses and repairs, and increased overall fluency. Additionally, the post-test showed a higher percentage of error-free clauses compared to the pre-test, reflecting a substantial enhancement in grammatical accuracy. This suggests that the intervention had a positive impact on the participants’ ability to produce grammatically accurate and error-free clauses. These outcomes suggest that the reading assistant software effectively enhances both the fluency and grammatical accuracy of speech production in EFL learners, underscoring its potential benefits in language education contexts.